94.7k views
2 votes
Use the function f(x) = 2x3 -3x2 + 7 to complete the exercises

f(-1) =
f(1) =
f(2) =

1 Answer

4 votes

Answer:

  • f(-1) = 8
  • f(1) = 6
  • f(2) = 11

Explanation:

Given the function

f(x) = 2x³ -3x²+ 7

putting x=-1 to find f(-1)

f(-1) = 2(-1)³ -3(-1)²+ 7

= -2 + 3 + 7

= 8

putting x=1 to find f(1)

f(1) = 2(1)³ -3(1)²+ 7

= 2 - 3 + 7

= 6

putting x=2 to find f(2)

f(2) = 2(2)³ -3(2)²+ 7

= 16 - 12 + 7

= 11

Therefore,

  • f(-1) = 8
  • f(1) = 6
  • f(2) = 11
User Mannicken
by
4.8k points